ASPEK BIOLOGI IKAN KERAPU EKOR PUTIH (Epinephelus areolatus FORSSKAL, 1775) DI PERAIRAN DESA GALESONG KOTA KABUPATEN TAKALAR - Sitepu, Farida Gassing (Hasanuddin University, 2014)
Areolate grouper is kinds of fish that exploited by fisherman in Galesong Kota Village. This is causedthe decreased of it population and concerned to be extinct, therefore conservation is in efforts. This researchaims to find out some biological aspect of areolate grouper such as, sex ratio, gonad maturity level(GML),gonad maturity index(GMI), and first time size of mature gonad. This research held on March-May 2013 inGalesong Kota Village, Takalar Regency. Applied method in this reseach is Descriptive Method. Gonadobservation conducted morphologically. The results of the showed that morphological ratio between female,transition and male 8 : 1 : 9. GML I, III, IV, and IX dominant in March, GML II, VI, VII, VIII, X, and GML Vdominant in May. Highest GMI rate of female phase is on May, with GMI average 0,6600%, highest GMI phasetransition on April with GMI average 1,3619%, and highest GMI of male phase is on April with GMI average0,7709%. Areolate grouper size of female phase for the first time of mature gonad at length of 230 mm andweight of 223 gr and male phase at body length of 290 mm and weught of 284 gr. Keywords : areolate grouper, biological aspect, Galesong Kota